ASSESSMENT OF ANTIGENIC CROSS - REACTIVITY AMONGST STRONGYLID NEMATODES USING OUCHTERLONY DOUBLE IMMUNODIFFUSION TEST - Arunkumar, S; Sharma , R L (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
Cross-reactivity amongst strongylid nematodes viz., Haemonchus contortus, Oesophagostomum columbianum and Bunostomum trigonocephalum was evaluated by Ouchterlony double immunodiffusion test (DID). Two antigens namely soluble extract antigen (SEA) and gut integral membrane antigen (GIMA) were probed with rabbit hyper immune sera raised against SEA of three referral nematodes to discern out the image of identity. The immunoreactivity pattern of referral nematode antigens showed generally 2-3 precipitation lines with homologous and 1 precipitation line with heterologous sera. Evidently these results suggested the existence of cross-reacting molecules among the SEA and GIMA of referral nematodes.